Perilaku Pemilih Menjelang Pemilu 2019 - Agus Machfud Fauzi (Universitas Nahdlatul Ulama Surabaya, 2019)
Voter behavior is the main attraction in the process of 2019 national political contestation. At the beginning of the political journey in Indonesia he became a contender for various ideologies that were allowed to become participants in the elections in 1955. The attraction between political parties made voters respond and respond to it. in the Old Order voters were free to make choices in accordance with the political orientation that was followed. Shifting to the New Order Pemillih was limited in its choices because only two political parties and groups of works were allowed to live. The presence of the Reform Order reopened people's choices which made voter behavior follow the changing times. Towards the 2019 Election voter behavior is more interesting to discuss because of the dynamics accompanying.